ANALISIS KEBIJAKAN NASIONAL TENTANG PENUNTASAN WAJIB BELAJAR PENDIDIKAN DASAR 9 TAHUN PERIODE 2003 - 2006 DI WILAYAH PROVINSI DKI JAKARTA - SHOLEH, MUNAWAR (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The purpose of this research is to analyze the implementation of national policies on the accomplishment of 9 year compulsory basic education period 2003 â 2006. Research was conducted in implementation of national policy in DKI Jakarta Province. The focus of this analysis is on the accomplishment of 9 year compulsory basic education and the equalization of basic education and the public participation on basic education program.The analysis is about the implementation of the policy rather than policy content. The analysis of the legal aspects starting from the Laws, President Decree, Ministery Decision, and Ministery Order. Descriptive and explanation method were used to analyze secondary and primary data. The results of the research are as follows: (1) the government commitsÂ  highly on the accomplishment of 9 year compulsory education; (2) the implentative policies are the realization of the commitment of government on accomplishment of 9 year compulsory education; (3) the government of DKI Jakarta Province has wellÂ  implemented the national policies on accomplishment of 9 year compulsory education, but it hasÂ  achieved less than 95% for Gross EnrollmentÂ  Rate at elementary school level and less than 80% for Net EnrollmentÂ  Rate at elementary school and secondary school levels; (4) the public participation on elementary school level is low. Based on those findings, it could be concluded that the government of DKI Jakarta Province has implemented the accomplishment of the 9 year compulsory basic education policy in equalization of basic education program and improvement of public participation on elementary schools. The government of DKI Jakarta Province has accomplished the Gross Enrollment Rate but the improvement of the quality of the basic education is stillÂ  inequitable.Keywords: national policies, and government commits